Usefulness of virtual bronchoscopy in evaluation of suspected foreign body in tracheobronchial tree - Srivastava, Mohit; Tyagi, Sushant (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Background: Airway foreign bodies remain a diagnostic challenge to health care professionals. They can become life threatening emergencies that require immediate intervention or can go unnoticed for weeks and even months. Every effort should be made to avoid a delay in diagnosis because this may lead to a notable increase in complication rates. The objective of this study is to investigate the usefulness of virtual bronchoscopy in evaluation of suspected foreign body aspiration in tracheobronchial tree. Methods: This retrospective & prospective study of 100 patients is conducted in the department of otorhinolaryngology & Head & Neck Surgery, Saraswathi Institute of Medical sciences, Hapur, Uttar Pradesh, India; from August 2011 to August 2015. Cases referred from department of paediatrics, with history of sudden breathlessness, sudden onset of cough with or without cyanosis & with or without pyrexia. Results: In our studies highest incidence of foreign bodies i.e. 61% were seen in the children between the age of 1-5 yrs 73% cases were male children while 27% were female children. Incidence of FB was quite higher in low socio economic status group (63%) as compared to middle class (34%) In our studies maximum no of cases i.e. 31% were betel nut followed by custard apple 22%. Others include gram seed (8%), tamarind seed (6%), coconut (5%) and ground nut (10%). In our studies, majority of FB in air passage were in right main bronchus 57% followed by upper air passage (22%) & 21% in left main bronchus. Conclusions: FB aspiration is an anaesthetic emergency and senior help should be sought early. Techniques should be tailored to the clinical context but spontaneous respiration should be maintained wherever possible. VB is proving to be a very helpful investigation modality in patients of a compromised airway. VB works well in planning the further management protocol not only in conjunction with other modalities but also on its own It is accurate but its accuracy is not 100% because of false positive & false negative results. VB will never replace actual bronchoscopy (gold standard) but it can assist & complement it.